Trade Liberalization and the Skill Premium: A Local Labor Markets Approach - Dix-Carneiro, Rafael; Kovak, Brian K. (American Economic Review, 2015)
We develop a specific-factors model of regional economies that includes two types of workers, skilled and unskilled. The model delivers a simple equation relating trade-induced local shocks to changes in local skill premia. We apply the methodology to Brazil's early 1990s trade liberalization and find statistically significant but modest effects of liberalization on the evolution of the skill premium between 1991 and 2010. The methodology uses widely available household survey data and can easily be applied to other countries and liberalization episodes.